Production and preparation method capable of eliminating internal stress of copper-steel bimetallic composite material
Through additive manufacturing technology and subsequent processing technology, the problem of residual stress at the interface in copper-steel bimetallic composites is solved, and the mechanical properties and service life of the material are significantly improved.
Patent Information
- Application Number
- CN202510286836.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-12
AI Technical Summary
In the preparation process of traditional copper-steel bimetal composite materials, segregation is prone to occur at the interface of copper-steel, which leads to the accumulation of residual stresses and affects the mechanical properties and service life of the material.
Additive manufacturing technology is used to prepare copper-steel bimetallic composite materials. By controlling heat source parameters and scanning paths, alloy elements are added to the copper-steel interface, adjust the cooling rate and refine the grains, and combine heat treatment, ultrasonic impact treatment and vibration treatment to gradually eliminate internal stress.
It significantly reduces the residual stress inside the copper-steel bimetallic composite material, improves the fatigue resistance and service life of the material, and improves the metallurgical bond quality and overall mechanical properties of the interface.
Smart Images

Figure CN119772205A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal preparation, and in particular to a production method capable of eliminating the internal stress of a copper-steel bimetallic composite material. Background Art
[0002] Copper-steel bimetallic composites have broad application prospects in many fields because they have the excellent electrical conductivity and thermal conductivity of copper and the high strength of steel. However, when manufacturing copper-steel bimetallic composites, traditional preparation processes are prone to segregation at the copper-steel interface, resulting in the accumulation of residual stress, which affects the mechanical properties and service life of the material. The existence of this residual stress will not only reduce the fatigue resistance of the material, but may also cause early failure of the material during use.
[0003] At present, the methods for eliminating residual stress mainly include heat treatment and mechanical processing. Although heat treatment can effectively release residual stress, it may lead to a decrease in material performance, and the treatment process is complicated and costly. Mechanical processing methods such as shot peening and ultrasonic impact treatment can produce beneficial residual compressive stress on the surface of the material, but for complex multilayer structures such as copper-steel bimetallic composite materials, their effects are limited and difficult to process uniformly. In addition, these methods still have certain limitations in practical applications. For example, heat treatment may cause the grain growth of the material, thereby reducing the strength and hardness of the material, while mechanical processing methods may cause damage to the surface of the material, affecting the surface quality of the material.
[0004] In recent years, with the development of additive manufacturing technology, it has been applied to the preparation of copper-steel bimetallic composites. Additive manufacturing technology can realize the rapid manufacturing of complex structures and effectively reduce metallurgical defects at the interface by precisely controlling the heat input and cooling rate during the molding process. However, although additive manufacturing technology has improved the interface bonding quality to a certain extent, residual stress may still be generated during the preparation process, especially at the copper-steel interface. The existence of this residual stress may lead to early failure of the material.
[0005] In summary, developing a production and preparation method that can effectively eliminate the internal stress of copper-steel bimetallic composite materials is of great significance for improving the performance and service life of the material. Summary of the invention
[0006] The purpose of the present invention is to solve the problem that the residual stress in the prior art is not completely eliminated, which affects the material performance and life, and to propose a production and preparation method that can eliminate the internal stress of the copper-steel bimetallic composite material.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme: a production method capable of eliminating the internal stress of a copper-steel bimetallic composite material, comprising the following steps: Step S1, preparing a copper-steel bimetallic composite material by using additive manufacturing technology, and controlling the heat source parameters and scanning path to achieve regulation of the interface structure; Step S2, adding alloy elements at the copper-steel interface to promote diffusion and uniform distribution of the elements and reduce segregation at the interface; Step S3, during the additive manufacturing process, by adjusting the cooling rate, the grains at the interface are refined to reduce the stress concentration caused by the grain size difference; Step S4, heat treating the copper-steel bimetallic composite material after additive manufacturing, and eliminating internal stress by controlling the heat treatment temperature and time; Step S5, performing ultrasonic impact treatment on the copper-steel bimetallic composite material after the heat treatment, so as to cause compressive plastic deformation of the composite material by high-frequency impact and release residual stress; Step S6, vibrating the copper-steel bimetallic composite material after the ultrasonic impact treatment to make the material vibrate at a resonant frequency to release stress; Step S7, detecting the distribution of internal stress by ultrasonic detection technology to ensure that the internal stress of the copper-steel bimetallic composite material is effectively eliminated.
[0008] Furthermore, in step S1, the following sub-steps are also included: S1-1, selecting additive manufacturing technology according to the application needs and performance requirements of the copper-steel bimetallic composite material, wherein the additive manufacturing technology includes laser additive manufacturing, electron beam additive manufacturing, and arc additive manufacturing; S1-2, designing scanning path and heat source parameters to achieve regulation of interface structure, wherein the heat source parameters include laser power, scanning speed, electron beam energy, and arc current; S1-3, real-time monitoring of the molding state and interface quality of the material, using laser displacement sensors and thermal imagers to detect the molten pool temperature, molten pool size and interlayer bonding of the material, and adjusting the heat source parameters.
[0009] Furthermore, in step S2, the following sub-steps are also included: S2-1, adding an appropriate amount of alloying elements at the copper-steel interface, which can form a solid solution or intermetallic compound with copper and steel to promote the diffusion and uniform distribution of the elements, and the alloying elements include nickel, chromium, molybdenum, iron, manganese and silicon; S2-2, by optimizing the addition amount of alloying elements, controlling the chemical composition gradient at the interface, and reducing the interface segregation phenomenon caused by composition differences, the addition amount is 0.5% to 5% of the total weight at the copper-steel interface; S2-3, using stirring, vibration and chemical plating to evenly distribute the alloy elements at the interface, the stirring time is 10 minutes to 30 minutes, and the rated frequency of the vibration is 20 Hz to 50 Hz.
[0010] Furthermore, in step S3, the following sub-steps are also included: S3-1, in the additive manufacturing process, the cooling rate is adjusted by controlling the temperature and flow rate of the cooling medium to refine the grains at the interface, wherein the temperature of the cooling medium is controlled at 20° C. to 40° C. and the flow rate is 1 L / min to 5 L / min; S3-2, during the cooling process, use multi-point temperature sensors to monitor the temperature changes at the interface in real time, and dynamically adjust the cooling parameters according to the monitoring data to ensure that the cooling process is uniform and stable, and avoid interface defects caused by local overcooling or overheating; S3-3, after cooling is completed, metallographic analysis is performed on the cooled material to check the grain size and structural uniformity at the interface, and the metallographic analysis is performed using an optical microscope.
[0011] Furthermore, in step S4, the following sub-steps are also included: S4-1, placing the copper-steel bimetallic composite material after additive manufacturing into a heat treatment furnace, and heating it to a preset heat treatment temperature at a certain heating rate, wherein the heating rate is 10°C / min to 30°C / min, and the temperature is 500°C to 700°C; S4-2, maintaining the material at the heat treatment temperature for a certain period of time to fully release the residual stress inside the material, wherein the period of time is 1 hour to 4 hours; S4-3, according to the performance requirements of the material and the heat treatment effect, the heat treatment temperature and the heat preservation time are adjusted within the adjustment range, and the adjustment range is the heat treatment temperature ± 50 ° C, and the heat preservation time ± 1 hour; S4-4, after the insulation is completed, the material is cooled to room temperature at a certain cooling rate, and the cooling rate is 10°C / min to 50°C / min.
[0012] Furthermore, in step S5, the following sub-steps are also included: S5-1, adjusting the parameters of the ultrasonic impact equipment according to the thickness and hardness of the material, the parameters including amplitude, frequency, and impact force, the amplitude being 10 μm to 50 μm, the frequency being 20 kHz to 50 kHz, and the impact force being 100 N to 500 N; S5-2, performing ultrasonic impact treatment on the surface of the copper-steel bimetallic composite material according to a preset impact path and impact times, so as to cause compressive plastic deformation on the surface of the material, eliminate the surface residual tensile stress, and form beneficial residual compressive stress on the surface, wherein the impact times are 4 to 10 times; S5-3, during the ultrasonic impact treatment process, strain gauges and displacement sensors are used to monitor the stress changes and deformation of the material surface, and the impact parameters are adjusted in real time to ensure that the impact treatment is uniform and effective.
[0013] Furthermore, in step S6, the following sub-steps are also included: S6-1, according to the structure and size of the copper-steel bimetallic composite material, adjust the vibration frequency and amplitude of the vibration aging equipment to match the resonant frequency of the material, the vibration frequency is 10Hz to 50Hz, and the amplitude is 0.1mm to 1mm; S6-2, fix the material on the vibration aging equipment, perform vibration treatment on the material, make the material vibrate at the resonance frequency, and release the internal residual stress; S6-3, during the vibration treatment process, real-time monitoring of material stress changes and vibration response, using accelerometers and strain gauges to record vibration data to ensure the uniformity and effectiveness of the vibration treatment; S6-4, dynamically adjust the vibration parameters according to the monitoring results to ensure that the material is vibrated under the best resonance conditions to release the internal stress to the maximum extent.
[0014] Furthermore, in step S7, the following sub-steps are also included: S7-1, using ultrasonic testing technology, setting testing parameters, and performing internal stress testing on the treated copper-steel bimetallic composite material, wherein the testing parameters include frequency, pulse width, gain, probe angle, and coupling medium; S7-2, during the testing process, record the stress distribution of the material, use ultrasonic signal analysis software to analyze the data, evaluate the stress relief effect, and determine whether the internal stress of the material is within the controllable range; S7-3, if the test results show that the internal stress exceeds the controllable range, repeat steps S4-S6 to further optimize and adjust the production process until the internal stress is effectively eliminated and the material performance is stable and reliable.
[0015] The beneficial effects brought about by the technical solution provided by the present invention include at least: The present invention adopts additive manufacturing technology to prepare copper-steel bimetallic composite materials, and realizes the regulation of interface organizational structure by controlling heat source parameters and scanning paths; alloy elements are added at the copper-steel interface to promote the diffusion and uniform distribution of elements and reduce segregation at the interface; in the additive manufacturing process, the cooling rate is adjusted to refine the grains at the interface and reduce the stress concentration caused by the difference in grain size; the copper-steel bimetallic composite materials after additive manufacturing are heat-treated and the internal stress is eliminated by controlling the heat treatment temperature and time; the copper-steel bimetallic composite materials after the heat treatment are subjected to ultrasonic impact treatment and high-frequency impact is used to cause the composite materials to produce compressive plastic deformation and release residual stress; the copper-steel bimetallic composite materials after the ultrasonic impact treatment are vibrated to cause the material to vibrate at the resonant frequency and release stress; the distribution of internal stress is detected by ultrasonic detection technology to ensure that the internal stress of the copper-steel bimetallic composite materials is effectively eliminated.
[0016] The present invention can significantly reduce the residual stress inside the copper-steel bimetallic composite material by optimizing the additive manufacturing process parameters and introducing subsequent processing technology, effectively eliminate the residual tensile stress inside the material, and form beneficial residual compressive stress on the surface, thereby improving the fatigue resistance and service life of the material.
[0017] The present invention adds an appropriate amount of alloy elements at the copper-steel interface and optimizes the interface structure through a heat treatment process, which significantly improves the metallurgical bonding quality of the interface, not only reduces the segregation phenomenon at the interface, but also enhances the strength and toughness of the interface, thereby significantly improving the overall mechanical properties of the material.
[0018] The production and preparation method provided by the present invention has a simple process flow, is easy to operate, does not require complicated equipment and high costs, reduces the complicated links in traditional processes, reduces production costs, improves production efficiency, and has high industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 A flow chart of a method provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0021] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of the production and preparation method of a copper-steel bimetallic composite material that can eliminate the internal stress of the present invention, its specific implementation method, structure, characteristics and effects, in combination with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "another embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable form.
[0022] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0023] The following examples are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0024] The following is a specific scheme of a production and preparation method for eliminating the internal stress of a copper-steel bimetallic composite material provided by the present invention, which is described in detail with reference to the accompanying drawings.
[0025] See also Figure 1 , which shows a method flow chart of a production method for eliminating internal stress of a copper-steel bimetallic composite material provided by an embodiment of the present invention, the method comprising the following steps: Step S1, preparing a copper-steel bimetallic composite material by using additive manufacturing technology, and controlling the heat source parameters and scanning path to achieve regulation of the interface structure; Wherein step S1 also includes the following sub-steps: S1-1, selecting additive manufacturing technology according to the application needs and performance requirements of the copper-steel bimetallic composite material, wherein the additive manufacturing technology includes laser additive manufacturing, electron beam additive manufacturing, and arc additive manufacturing; S1-2, designing scanning path and heat source parameters to achieve regulation of interface structure, wherein the heat source parameters include laser power, scanning speed, electron beam energy, and arc current; S1-3, real-time monitoring of the molding state and interface quality of the material, using laser displacement sensors and thermal imagers to detect the molten pool temperature, molten pool size and interlayer bonding of the material, and adjusting the heat source parameters.
[0026] It should be noted that laser additive manufacturing (LAM): the laser power range is 200W to 500W, and the scanning speed is 500mm / min to 1500mm / min. It is suitable for the preparation of high-precision, small-size copper-steel bimetallic composites. Laser additive manufacturing can provide high energy density, precisely control the molten pool size and temperature, and is suitable for manufacturing complex geometries.
[0027] Electron beam additive manufacturing (EBAM): The electron beam energy range is 100W to 300W, and the scanning speed is 300mm / min to 800mm / min. It is suitable for materials that require high energy absorption. Electron beam additive manufacturing can be carried out in a vacuum environment to reduce oxidation and is suitable for manufacturing environmentally sensitive materials.
[0028] Electric Arc Additive Manufacturing (WAAM): The arc current ranges from 80A to 150A, and the welding speed ranges from 200mm / min to 600mm / min. It is suitable for the preparation of large and complex-shaped copper-steel bimetallic composites. Electric Arc Additive Manufacturing has a high deposition efficiency and is suitable for the manufacture of large structural parts.
[0029] Laser power: controls the energy output of the laser, affecting the temperature and size of the molten pool. Laser power usually ranges from 200W to 500W.
[0030] Scanning speed: controls the speed at which the laser or electron beam moves on the material surface, affecting the cooling rate and grain size of the molten pool. The scanning speed range is usually 500mm / min to 1500mm / min.
[0031] Electron beam energy: Controls the energy output of the electron beam, affecting the temperature and size of the molten pool. Electron beam energy typically ranges from 100W to 300W.
[0032] Arc current: controls the energy output of the arc, affecting the temperature and size of the weld pool. The arc current range is usually 80A to 150A.
[0033] Scanning path: It can be a straight line, spiral line or complex geometric path. The specific path is optimized according to the shape and performance requirements of the material to ensure uniform forming of the material and metallurgical bonding at the interface.
[0034] Laser displacement sensor: used to detect the molten pool temperature, molten pool size and interlayer bonding of the material. It can provide real-time feedback on the three-dimensional size and temperature distribution of the molten pool to ensure the stability and uniformity of the molten pool.
[0035] Thermal imager: used to monitor the temperature distribution of the molten pool to ensure that the temperature of the molten pool is uniform and avoid local overheating or overcooling.
[0036] Step S2, adding alloy elements at the copper-steel interface to promote diffusion and uniform distribution of the elements and reduce segregation at the interface; Wherein step S2 also includes the following sub-steps: S2-1, adding an appropriate amount of alloying elements at the copper-steel interface, which can form a solid solution or intermetallic compound with copper and steel to promote the diffusion and uniform distribution of the elements, and the alloying elements include nickel, chromium, molybdenum, iron, manganese and silicon; S2-2, by optimizing the addition amount of alloying elements, controlling the chemical composition gradient at the interface, and reducing the interface segregation phenomenon caused by composition differences, the addition amount is 0.5% to 5% of the total weight at the copper-steel interface; S2-3, using stirring, vibration and chemical plating to evenly distribute the alloy elements at the interface, the stirring time is 10 minutes to 30 minutes, and the rated frequency of the vibration is 20 Hz to 50 Hz.
[0037] It should be noted that nickel: added in an amount of 1% to 3%, can form a good solid solution with copper and steel, improve the metallurgical compatibility of the interface, and promote the diffusion of elements.
[0038] Chromium: The addition amount is 0.5% to 2%, which can improve the material's oxidation resistance and corrosion resistance, and enhance the hardness and strength of the interface.
[0039] Molybdenum: The addition amount is 0.1% to 1%, which can effectively strengthen the solid solution and precipitation strengthening elements, improve the strength and toughness of the material, and improve the crack resistance of the interface.
[0040] Iron: Added in an amount of 0.5% to 2%, it can promote the metallurgical bonding between copper and steel and reduce the brittle phase at the interface.
[0041] Manganese: The addition amount is 0.1% to 1%, which can improve the strength and toughness of the material and improve the crack resistance of the interface.
[0042] Silicon: The addition amount is 0.1% to 0.5%, which can improve the material's oxidation resistance and corrosion resistance, and improve the hardness and strength of the interface.
[0043] Stirring: Use mechanical stirring to evenly distribute the alloy elements at the interface. The stirring time is 10 to 30 minutes to ensure that the alloy elements are fully mixed.
[0044] Vibration: Vibration treatment is used to evenly distribute the alloy elements at the interface. The vibration frequency is 20Hz to 50Hz and the vibration time is 10 minutes to 30 minutes to ensure the uniform distribution of the alloy elements.
[0045] Chemical plating: a technology that forms a metal coating on the surface of a substrate through a chemical reaction. It does not require an external power source, but relies on a chemical reduction reaction to reduce metal ions to metals and deposit them on the surface of the substrate. It can achieve uniform deposition of alloy elements at the interface of copper-steel bimetallic composite materials, improve the metallurgical bonding properties of the interface, reduce segregation, and thus improve the overall performance of the material.
[0046] Step S3, in the additive manufacturing process, by adjusting the cooling rate, the grains at the interface are refined to reduce the stress concentration caused by the grain size difference; Wherein step S3 also includes the following sub-steps: S3-1, in the additive manufacturing process, the cooling rate is adjusted by controlling the temperature and flow rate of the cooling medium to refine the grains at the interface, wherein the temperature of the cooling medium is controlled at 20° C. to 40° C. and the flow rate is 1 L / min to 5 L / min; S3-2, during the cooling process, use multi-point temperature sensors to monitor the temperature changes at the interface in real time, and dynamically adjust the cooling parameters according to the monitoring data to ensure that the cooling process is uniform and stable, and avoid interface defects caused by local overcooling or overheating; S3-3, after cooling is completed, metallographic analysis is performed on the cooled material to check the grain size and structural uniformity at the interface, and the metallographic analysis is performed using an optical microscope.
[0047] It should be noted that the cooling medium: water and air are used. Water has a better cooling effect, but it may cause rapid cooling of the material surface and generate thermal stress; air cooling is relatively gentle, but the cooling rate is slower.
[0048] Temperature control: The temperature of the cooling medium is controlled at 20℃ to 40℃. Lower temperatures can speed up the cooling rate, but may cause the material surface to be overcooled and generate thermal stress; higher temperatures can slow down the cooling rate, but may cause the material to be overheated inside and affect the grain refinement effect.
[0049] Flow control: The flow rate of the cooling medium is controlled at 1L / min to 5L / min. A larger flow rate can speed up the cooling rate, but may cause the material surface to be overcooled; a smaller flow rate can slow down the cooling rate, but may cause the material to be overheated inside.
[0050] Multi-point temperature sensor: Multiple temperature sensors are arranged at the interface to monitor the temperature changes of the material in real time. Multi-point monitoring can provide more comprehensive temperature distribution information to ensure the uniformity of the cooling process.
[0051] Dynamic adjustment: According to the monitoring data, the temperature and flow of the cooling medium are dynamically adjusted to ensure the uniformity of the cooling process. If the temperature at a certain point is too high, the cooling flow in that area can be appropriately increased; if the temperature at a certain point is too low, the cooling flow in that area can be appropriately reduced.
[0052] Optical microscope: Use an optical microscope to observe the microstructure of the material and measure the grain size and organizational uniformity. Optical microscopes can provide high-resolution images for easy observation and analysis.
[0053] Grain size measurement: Use an optical microscope to measure the grain size to ensure that the grain size at the interface is uniform and small. Small grain size can improve the strength and toughness of the material and reduce stress concentration.
[0054] Microstructure uniformity inspection: Check the microstructure uniformity of the material to ensure that the material has a good microstructure after cooling and reduce stress concentration caused by grain size differences.
[0055] Step S4, heat treating the copper-steel bimetallic composite material after additive manufacturing, and eliminating internal stress by controlling the heat treatment temperature and time; Wherein step S4 also includes the following sub-steps: S4-1, placing the copper-steel bimetallic composite material after additive manufacturing into a heat treatment furnace, and heating it to a preset heat treatment temperature at a certain heating rate, wherein the heating rate is 10°C / min to 30°C / min, and the temperature is 500°C to 700°C; S4-2, maintaining the material at the heat treatment temperature for a certain period of time to fully release the residual stress inside the material, wherein the period of time is 1 hour to 4 hours; S4-3, according to the performance requirements of the material and the heat treatment effect, the heat treatment temperature and the heat preservation time are adjusted within the adjustment range, and the adjustment range is the heat treatment temperature ± 50 ° C, and the heat preservation time ± 1 hour; S4-4, after the insulation is completed, the material is cooled to room temperature at a certain cooling rate, and the cooling rate is 10°C / min to 50°C / min.
[0056] It should be noted that the choice of heating rate has an important influence on the thermal stress distribution of the material. If the heating rate is too fast and the temperature difference between the inside and outside of the material is too large, it may lead to an increase in thermal stress and even cause deformation or cracking of the material. Selecting a heating rate of 10℃ / min to 30℃ / min can ensure heating efficiency while avoiding thermal stress caused by excessive temperature difference.
[0057] Selection of preset temperature: The temperature range of 500℃ to 700℃ is set based on the characteristics of copper-steel bimetallic composite materials. The recrystallization temperature of copper is about 300℃ to 400℃, while the recrystallization temperature of steel is usually higher. Within this temperature range, the residual stress at the interface of copper and steel can be released through atomic diffusion and recrystallization processes, while avoiding the degradation of material properties (grain growth, reduced hardness) that may be caused by excessively high temperatures.
[0058] Choice of insulation time: The length of insulation time determines the degree of residual stress release inside the material. Longer insulation time can release residual stress more fully, but too long insulation time may lead to unstable material properties. Choosing an insulation time of 1 to 4 hours can ensure sufficient stress release while avoiding excessive decline in material properties.
[0059] Necessity of adjustment: Due to differences in material composition, structure and additive manufacturing process, different copper-steel bimetallic composites may require different heat treatment parameters. By adjusting the temperature and holding time, the heat treatment effect can be optimized to ensure that the material's performance is optimal.
[0060] Selection of adjustment range: The temperature adjustment range of ±50℃ and the time adjustment range of ±1 hour are set based on the experience and experimental data in actual production, which can cover the heat treatment requirements of most copper-steel bimetallic composite materials while avoiding unstable material properties caused by excessive adjustment range.
[0061] Selection of cooling rate: If the cooling rate is too fast, new residual stress may be generated inside the material; if the cooling rate is too slow, it may lead to a decrease in material performance (grain growth). Selecting a cooling rate of 10℃ / min to 50℃ / min can avoid the generation of new residual stress while ensuring the performance of the material.
[0062] Step S5, performing ultrasonic impact treatment on the copper-steel bimetallic composite material after the heat treatment, so as to cause compressive plastic deformation of the composite material by high-frequency impact and release residual stress; Wherein, in step S5, the following sub-steps are also included: S5-1, adjusting the parameters of the ultrasonic impact equipment according to the thickness and hardness of the material, the parameters including amplitude, frequency, and impact force, the amplitude being 10 μm to 50 μm, the frequency being 20 kHz to 50 kHz, and the impact force being 100 N to 500 N; S5-2, performing ultrasonic impact treatment on the surface of the copper-steel bimetallic composite material according to a preset impact path and impact times, so as to cause compressive plastic deformation on the surface of the material, eliminate the surface residual tensile stress, and form beneficial residual compressive stress on the surface, wherein the impact times are 4 to 10 times; S5-3, during the ultrasonic impact treatment process, strain gauges and displacement sensors are used to monitor the stress changes and deformation of the material surface, and the impact parameters are adjusted in real time to ensure that the impact treatment is uniform and effective.
[0063] It should be noted that ultrasonic impact treatment is a process that uses high-frequency impact to produce compressive plastic deformation on the material surface, thereby releasing residual stress and improving the surface properties of the material. It aims to eliminate the residual tensile stress on the surface of the copper-steel bimetallic composite material and form beneficial residual compressive stress on the surface, thereby improving the material's fatigue resistance and service life.
[0064] Ultrasonic impact equipment includes hand-held ultrasonic impact tools: amplitude: 10μm to 50μm, frequency: 20kHz to 50kHz, impact force: 100N to 500N; fixed ultrasonic impact equipment: amplitude: 20μm to 80μm, frequency: 15kHz to 40kHz, impact force: 200N to 800N; automated ultrasonic impact system: amplitude: 10μm to 60μm, frequency: 20kHz to 50kHz, impact force: 150N to 600N; portable ultrasonic impact equipment: amplitude: 10μm to 40μm, frequency: 20kHz to 40kHz, impact force: 100N to 300N.
[0065] Amplitude: The amplitude determines the size of the impact energy. A larger amplitude can provide stronger impact energy, thereby more effectively eliminating residual stress. However, too large an amplitude may cause damage to the material surface. Selecting an amplitude range of 10μm to 50μm can ensure the impact effect while avoiding damage to the material surface.
[0066] Frequency: The frequency determines the frequency of the impact. A higher frequency can improve the impact efficiency, but too high a frequency may lead to increased energy consumption of the equipment and unstable impact effect. Selecting a frequency range of 20kHz to 50kHz can improve the operating efficiency of the equipment while ensuring the impact effect.
[0067] Impact force: The impact force determines the intensity of the impact. A larger impact force can more effectively eliminate residual stress, but excessive impact force may cause damage to the material surface. Selecting an impact force range of 100N to 500N can ensure the impact effect while avoiding damage to the material surface.
[0068] Influence of material thickness and hardness: The thickness and hardness of the material will affect the selection of impact parameters. Thicker or harder materials require greater impact force and amplitude, while thinner or softer materials require smaller impact force and amplitude.
[0069] Impact path: Covering the key areas of the material surface, especially the stress concentration areas, including welds and interfaces. Through reasonable impact path design, the uniformity and effectiveness of impact treatment can be ensured.
[0070] Number of impacts: The number of impacts determines the intensity of the impact treatment. A larger number of impacts can more effectively eliminate residual stress, but too many impacts may cause fatigue damage to the material surface. Selecting 4 to 10 impacts can ensure the impact effect while avoiding fatigue damage to the material surface.
[0071] Compressive plastic deformation and formation of residual compressive stress: Ultrasonic impact treatment causes compressive plastic deformation on the material surface through high-frequency impact, thereby eliminating the surface residual tensile stress and forming beneficial residual compressive stress on the surface. The residual compressive stress can improve the material's fatigue resistance and crack growth resistance.
[0072] Strain gauges and displacement sensors: Strain gauges and displacement sensors are commonly used stress monitoring equipment. Strain gauges can monitor the strain changes on the material surface in real time, and displacement sensors can monitor the deformation of the material surface. Through these monitoring devices, the effect of impact treatment can be understood in real time.
[0073] Real-time adjustment: During the impact treatment process, the stress and deformation on the material surface will continue to change. By real-time monitoring and adjusting the impact parameters, the uniformity and effectiveness of the impact treatment can be ensured, avoiding excessive or low local stress caused by improper parameter settings.
[0074] Adjustment method: According to the monitoring data, the amplitude, frequency and impact force parameters can be adjusted. If the stress in a certain area is monitored to be too high, the impact force or amplitude can be appropriately reduced; if the stress in a certain area is monitored to be too low, the impact force or amplitude can be appropriately increased.
[0075] Step S6, vibrating the copper-steel bimetallic composite material after ultrasonic impact treatment to make the material vibrate at a resonance frequency to release stress; Wherein, in step S6, the following sub-steps are also included: S6-1, according to the structure and size of the copper-steel bimetallic composite material, adjust the vibration frequency and amplitude of the vibration aging equipment to match the resonant frequency of the material, the vibration frequency is 10Hz to 50Hz, and the amplitude is 0.1mm to 1mm; S6-2, fix the material on the vibration aging equipment, perform vibration treatment on the material, make the material vibrate at the resonance frequency, and release the internal residual stress; S6-3, during the vibration treatment process, real-time monitoring of material stress changes and vibration response, using accelerometers and strain gauges to record vibration data to ensure the uniformity and effectiveness of the vibration treatment; S6-4, dynamically adjust the vibration parameters according to the monitoring results to ensure that the material is vibrated under the best resonance conditions to release the internal stress to the maximum extent.
[0076] It should be noted that the resonant frequency refers to the frequency at which the vibration energy reaches its maximum value when the material vibrates at this frequency. Selecting a suitable resonant frequency can release the residual stress inside the material to the maximum extent. The structure and size of the copper-steel bimetallic composite material determine that its resonant frequency range is 10Hz to 50Hz. If the frequency is too high or too low, it may not be able to effectively stimulate the resonance of the material, thereby reducing the effect of stress release.
[0077] Amplitude: The amplitude determines the intensity of the vibration. A larger amplitude can provide stronger vibration energy, thereby more effectively releasing residual stress. However, too large an amplitude may cause surface damage or structural deformation of the material. Selecting an amplitude range of 0.1mm to 1mm can ensure the vibration effect while avoiding damage to the material.
[0078] Structure and size: The structure and size of a material will affect its resonant frequency and amplitude. Larger materials may require lower vibration frequencies and larger amplitudes, while smaller materials may require higher vibration frequencies and smaller amplitudes.
[0079] Fixing method: The material needs to be firmly fixed on the vibration aging equipment to ensure that the material will not shift or loosen during the vibration process. The fixing method can be clamp fixing or bolt fixing. The specific choice depends on the shape and size of the material.
[0080] Vibration effect: When vibrating at the resonant frequency, the atoms and molecules inside the material will be subjected to periodic external forces, thereby promoting the release of residual stress. Vibration treatment can effectively reduce stress concentration inside the material and improve the stability and fatigue resistance of the material.
[0081] Accelerometers and strain gauges: Accelerometers can monitor the vibration acceleration of materials in real time, and strain gauges can monitor the strain changes on the surface of materials. Through accelerometers and strain gauges, the effect of vibration treatment can be understood in real time.
[0082] Real-time monitoring: During the vibration treatment process, the stress and vibration response inside the material will continue to change. Through real-time monitoring, the uniformity and effectiveness of the vibration treatment can be ensured, and local stress that is too high or too low due to improper vibration parameter settings can be avoided.
[0083] Data recording and analysis: The recorded vibration data can be processed and analyzed by professional data analysis software to evaluate the effect of the vibration treatment. By analyzing the acceleration and strain data, the stress distribution inside the material can be determined, thereby judging whether the vibration treatment has achieved the expected effect.
[0084] Adjustment method: According to the monitoring data, the vibration frequency, amplitude and vibration time parameters can be adjusted. If the stress in a certain area is monitored to be too high, the amplitude can be increased or the vibration time can be extended; if the stress in a certain area is monitored to be too low, the amplitude can be reduced or the vibration time can be shortened.
[0085] Dynamic adjustment: During the vibration treatment process, the internal structure and stress state of the material will continue to change. Therefore, it is necessary to dynamically adjust the vibration parameters based on real-time monitoring data to ensure the effect of the vibration treatment. Dynamic adjustment can avoid excessive or low local stress caused by improper parameter settings, thereby improving the uniformity and effectiveness of the vibration treatment.
[0086] Adjustment range: The adjustment range of vibration frequency is ±5Hz, and the adjustment range of amplitude is usually ±0.1mm. The adjustment range is set based on experience and experimental data in actual production, and can cover the vibration processing requirements of most copper-steel bimetallic composite materials.
[0087] Step S7, detecting the distribution of internal stress by ultrasonic detection technology to ensure that the internal stress of the copper-steel bimetallic composite material is effectively eliminated; Wherein, in step S7, the following sub-steps are also included: S7-1, using ultrasonic testing technology, setting testing parameters, and performing internal stress testing on the treated copper-steel bimetallic composite material, wherein the testing parameters include frequency, pulse width, gain, probe angle, and coupling medium; S7-2, during the testing process, record the stress distribution of the material, use ultrasonic signal analysis software to analyze the data, evaluate the stress relief effect, and determine whether the internal stress of the material is within the controllable range; S7-3, if the test results show that the internal stress exceeds the controllable range, repeat steps S4-S6 to further optimize and adjust the production process until the internal stress is effectively eliminated and the material performance is stable and reliable.
[0088] It should be noted that the frequency: the higher the frequency, the higher the resolution of ultrasound, but the weaker the penetration ability; the lower the frequency, the stronger the penetration ability, but the lower the resolution. The frequency of ultrasound is between 1 MHz and 10 MHz, which can ensure sufficient penetration depth while ensuring detection accuracy. The specific frequency selection depends on the thickness of the material and the detection depth. High-frequency ultrasound (5 MHz to 10 MHz) is suitable for thin plates or surface detection, and low-frequency ultrasound (1 MHz to 3 MHz) is suitable for thick plates or internal detection.
[0089] Pulse width: Pulse width affects the penetration ability and resolution of ultrasound. Short pulse width (10 ns to 50 ns) provides higher resolution but weaker penetration; long pulse width (100 ns to 500 ns) provides stronger penetration but lower resolution.
[0090] Gain: Gain is used to adjust the strength of the ultrasonic signal to ensure that the signal is not lost due to attenuation during the detection process. A higher gain can increase the sensitivity of the signal but may introduce noise; a lower gain can reduce noise but may reduce the sensitivity of the signal. It is usually between 20dB and 60dB, and the specific value is adjusted according to the attenuation characteristics of the material.
[0091] Probe angle: The probe angle affects the incident direction and reflection characteristics of the ultrasonic wave, and determines the propagation direction of the ultrasonic wave in the material. Selecting a probe angle of 45° to 70° can improve the detection accuracy while ensuring the detection coverage.
[0092] Coupling medium: Coupling medium is used to reduce the air gap between the probe and the material surface and improve the transmission efficiency of ultrasonic waves between the probe and the material surface. It includes water, glycerin, engine oil, and coupling agent. Selecting a suitable coupling medium can reduce signal attenuation and reflection and improve the detection effect.
[0093] Stress distribution recording: The stress distribution inside the material is recorded by ultrasonic testing equipment. The propagation speed and reflection characteristics of ultrasonic waves in the material will change due to different stress states, so the stress distribution can be evaluated by detecting these changes.
[0094] Data analysis: Use ultrasonic signal analysis software to process and analyze the recorded data. The analysis software can extract stress distribution characteristics through signal processing algorithms (Fourier transform) and generate stress distribution maps.
[0095] Evaluation criteria: According to the performance requirements and application background of the material, the evaluation criteria for stress relief are set. The internal stress should be lower than a certain proportion (10% to 20%) of the material's yield strength to ensure the stability and reliability of the material during use.
[0096] Controllable range: If the test results show that the internal stress is within the controllable range, it means that the stress elimination effect is good; if the internal stress exceeds the controllable range, the treatment process needs to be further optimized.
[0097] Repeating steps: If the internal stress exceeds the controllable range, it is necessary to perform heat treatment (step S4), ultrasonic impact treatment (step S5) and vibration treatment (step S6) again, and adjust the relevant process parameters according to the test results.
[0098] Optimization and adjustment: According to the ultrasonic test results, analyze the areas with uneven stress distribution or areas with excessive stress, and adjust the heat treatment temperature and time, ultrasonic impact parameters (amplitude, frequency, impact force, number of impacts) and vibration treatment parameters (vibration frequency, amplitude, vibration time) in a targeted manner.
[0099] Iterative optimization: Through multiple iterative optimizations, the process parameters are gradually adjusted until the internal stress is effectively eliminated and the material performance is stable and reliable. Ultrasonic testing is required again after each optimization to ensure the optimization effect.
[0100] In this way, a production and preparation method that can eliminate the internal stress of copper-steel bimetallic composite materials can effectively eliminate the internal stress of copper-steel bimetallic composite materials, while optimizing the interface structure, improving the overall performance of the material, and ensuring its stability and reliability in practical applications.
[0101] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A production method capable of eliminating internal stress of a copper-steel bimetallic composite material, characterized in that: The method includes: Step S1, preparing a copper-steel bimetallic composite material by using additive manufacturing technology, and controlling the heat source parameters and scanning path to achieve regulation of the interface structure; Step S2, adding alloy elements at the copper-steel interface to promote diffusion and uniform distribution of the elements and reduce segregation at the interface; Step S3, during the additive manufacturing process, by adjusting the cooling rate, the grains at the interface are refined to reduce the stress concentration caused by the grain size difference; Step S4, heat treating the copper-steel bimetallic composite material after additive manufacturing, and eliminating internal stress by controlling the heat treatment temperature and time; Step S5, performing ultrasonic impact treatment on the copper-steel bimetallic composite material after the heat treatment, so as to cause compressive plastic deformation of the composite material by high-frequency impact and release residual stress; Step S6, vibrating the copper-steel bimetallic composite material after the ultrasonic impact treatment to make the material vibrate at a resonant frequency to release stress; Step S7, detecting the distribution of internal stress by ultrasonic detection technology to ensure that the internal stress of the copper-steel bimetallic composite material is effectively eliminated.
2. A production method capable of eliminating internal stress of a copper-steel bimetallic composite material as claimed in claim 1, characterized in that: Wherein step S1 also includes the following sub-steps: S1-1, selecting additive manufacturing technology according to the application needs and performance requirements of the copper-steel bimetallic composite material, wherein the additive manufacturing technology includes laser additive manufacturing, electron beam additive manufacturing, and arc additive manufacturing; S1-2, designing scanning path and heat source parameters to achieve regulation of interface structure, wherein the heat source parameters include laser power, scanning speed, electron beam energy, and arc current; S1-3, real-time monitoring of the molding state and interface quality of the material, using laser displacement sensors and thermal imagers to detect the molten pool temperature, molten pool size and interlayer bonding of the material, and adjusting the heat source parameters.
3. A production method capable of eliminating internal stress of a copper-steel bimetallic composite material as claimed in claim 1, characterized in that: Wherein step S2 also includes the following sub-steps: S2-1, adding an appropriate amount of alloying elements at the copper-steel interface, which can form a solid solution or intermetallic compound with copper and steel to promote the diffusion and uniform distribution of the elements, and the alloying elements include nickel, chromium, molybdenum, iron, manganese and silicon; S2-2, by optimizing the addition amount of alloying elements, controlling the chemical composition gradient at the interface, and reducing the interface segregation phenomenon caused by composition differences, the addition amount is 0.5% to 5% of the total weight at the copper-steel interface; S2-3, using stirring, vibration and chemical plating to evenly distribute the alloy elements at the interface, the stirring time is 10 minutes to 30 minutes, and the rated frequency of the vibration is 20 Hz to 50 Hz.
4. A production method capable of eliminating internal stress of a copper-steel bimetallic composite material as claimed in claim 1, characterized in that: Wherein step S3 also includes the following sub-steps: S3-1, in the additive manufacturing process, the cooling rate is adjusted by controlling the temperature and flow rate of the cooling medium to refine the grains at the interface, wherein the temperature of the cooling medium is controlled at 20° C. to 40° C. and the flow rate is 1 L / min to 5 L / min; S3-2, during the cooling process, use multi-point temperature sensors to monitor the temperature changes at the interface in real time, and dynamically adjust the cooling parameters according to the monitoring data to ensure that the cooling process is uniform and stable, and avoid interface defects caused by local overcooling or overheating; S3-3, after cooling is completed, metallographic analysis is performed on the cooled material to check the grain size and structural uniformity at the interface, and the metallographic analysis is performed using an optical microscope.
5. The method for producing a copper-steel bimetallic composite material capable of eliminating internal stress according to claim 1, characterized in that: Wherein step S4 also includes the following sub-steps: S4-1, placing the copper-steel bimetallic composite material after additive manufacturing into a heat treatment furnace, and heating it to a preset heat treatment temperature at a certain heating rate, wherein the heating rate is 10°C / min to 30°C / min, and the temperature is 500°C to 700°C; S4-2, maintaining the material at the heat treatment temperature for a certain period of time to fully release the residual stress inside the material, wherein the period of time is 1 hour to 4 hours; S4-3, according to the performance requirements of the material and the heat treatment effect, the heat treatment temperature and the heat preservation time are adjusted within the adjustment range, and the adjustment range is the heat treatment temperature ± 50 ° C, and the heat preservation time ± 1 hour; S4-4, after the insulation is completed, the material is cooled to room temperature at a certain cooling rate, and the cooling rate is 10°C / min to 50°C / min.
6. A production method capable of eliminating internal stress of a copper-steel bimetallic composite material as claimed in claim 1, characterized in that: Wherein, in step S5, the following sub-steps are also included: S5-1, adjusting the parameters of the ultrasonic impact equipment according to the thickness and hardness of the material, the parameters including amplitude, frequency, and impact force, the amplitude being 10 μm to 50 μm, the frequency being 20 kHz to 50 kHz, and the impact force being 100 N to 500 N; S5-2, performing ultrasonic impact treatment on the surface of the copper-steel bimetallic composite material according to a preset impact path and impact times, so as to cause compressive plastic deformation on the surface of the material, eliminate the surface residual tensile stress, and form beneficial residual compressive stress on the surface, wherein the impact times are 4 to 10 times; S5-3, during the ultrasonic impact treatment process, strain gauges and displacement sensors are used to monitor the stress changes and deformation of the material surface, and the impact parameters are adjusted in real time to ensure that the impact treatment is uniform and effective.
7. A production method capable of eliminating internal stress of a copper-steel bimetallic composite material as claimed in claim 1, characterized in that: Wherein, in step S6, the following sub-steps are also included: S6-1, according to the structure and size of the copper-steel bimetallic composite material, adjust the vibration frequency and amplitude of the vibration aging equipment to match the resonant frequency of the material, the vibration frequency is 10Hz to 50Hz, and the amplitude is 0.1mm to 1mm; S6-2, fix the material on the vibration aging equipment, perform vibration treatment on the material, make the material vibrate at the resonance frequency, and release the internal residual stress; S6-3, during the vibration treatment process, real-time monitoring of material stress changes and vibration response, using accelerometers and strain gauges to record vibration data to ensure the uniformity and effectiveness of the vibration treatment; S6-4, dynamically adjust the vibration parameters according to the monitoring results to ensure that the material is vibrated under the best resonance conditions to release the internal stress to the maximum extent.
8. The method for producing a copper-steel bimetallic composite material capable of eliminating internal stress according to claim 1, characterized in that: Wherein, in step S7, the following sub-steps are also included: S7-1, using ultrasonic testing technology, setting testing parameters, and performing internal stress testing on the treated copper-steel bimetallic composite material, wherein the testing parameters include frequency, pulse width, gain, probe angle, and coupling medium; S7-2, during the testing process, record the stress distribution of the material, use ultrasonic signal analysis software to analyze the data, evaluate the stress relief effect, and determine whether the internal stress of the material is within the controllable range; S7-3, if the test results show that the internal stress exceeds the controllable range, repeat steps S4-S6 to further optimize and adjust the production process until the internal stress is effectively eliminated and the material performance is stable and reliable.
Citation Information
Patent Citations
Method for improving microstructure and performance of dissimilar alloy additive manufacturing interface through laser shock peening
CN110961635A
CoNiCrCu solid solution for heterogeneous interface bonding and preparation method and application thereof
CN111647791A
Copper / steel bimetal composite structural part combined with heat treatment process and preparation method of copper / steel bimetal composite structural part
CN113399937A
Copper-steel dissimilar metal connecting method
CN116652331A
Heat treatment method for manufacturing dissimilar structure through additive combination
CN117467912A